2003
DOI: 10.1128/iai.71.4.2110-2119.2003
|View full text |Cite
|
Sign up to set email alerts
|

Interactions betweenBrucella melitensisand Human Phagocytes: Bacterial Surface O-Polysaccharide Inhibits Phagocytosis, Bacterial Killing, and Subsequent Host Cell Apoptosis

Abstract: Brucellae are gram-negative intracellular pathogens which can survive and multiply within the phagocytic cells of their hosts and are resistant to the bactericidal action of serum. Brucella melitensis is considered the principal cause of human brucellosis (40,41) and is more virulent than B. abortus (42). These species may occur as either smooth or rough variants depending on the expression of O-polysaccharides (OPS) as a component of the bacterial outer membrane lipopolysaccharide (LPS). In rough strains expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 42 publications
(37 reference statements)
8
106
2
1
Order By: Relevance
“…A double antibody labeling procedure was employed to differentiate external bacteria (red) from internalized organisms (green) (data not shown). In agreement with previous reports [6,17,19], CA180 has greatly elevated binding capacity compared with S2308. The dynamics of internalization were determined according to the following criteria: i) fraction of cells containing internalized bacteria; ii) average bacterial burden per infected cell; and iii) fraction of cell-associated bacteria that was internalized (Fig.…”
Section: B Abortus Ops Affects Binding and Internalizationsupporting
confidence: 93%
See 3 more Smart Citations
“…A double antibody labeling procedure was employed to differentiate external bacteria (red) from internalized organisms (green) (data not shown). In agreement with previous reports [6,17,19], CA180 has greatly elevated binding capacity compared with S2308. The dynamics of internalization were determined according to the following criteria: i) fraction of cells containing internalized bacteria; ii) average bacterial burden per infected cell; and iii) fraction of cell-associated bacteria that was internalized (Fig.…”
Section: B Abortus Ops Affects Binding and Internalizationsupporting
confidence: 93%
“…With OPS, smooth Brucella S2308 invade macrophages via lipid rafts, which requires PI3-kinase and TLR4 signal and directs intracellular trafficking through a unique pathway to the replication niche [16]. Without OPS, rough Brucella mutant CA180 invade macrophages through a different pathway and are either destroyed as a result of macrophage activation or released prematurely as a result of cell death [17,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental studies using macrophage cell cultures and human macrophages showed that Brucella spp., an intracellular bacterium, triggered apoptotic cell death [26,27]. The genes regulating apoptosis are known as caspases [28].…”
Section: Discussionmentioning
confidence: 99%